Subcapsular Hematoma of The Liver Revealing RENDU-OSLER Disease: About A Pediatric Case - Khayi, F Z; ElBaz, M; ElHoudzi, J (British Journal of Healthcare and Medical Research, 2023)
RENDU-OSLER's disease is a rare hereditary disease of autosomal dominant transmission, it is a condition characterized by mucocutaneous and visceral telangiectasias; often revealed by recurrent epistaxis, hemostasis can be difficult. We report the observation of a 10-year-old girl who presented with chronic abdominal pain secondary to a subcapsular hematoma of the liver due to the rupture of an arteriovenous malformation falling within the framework of RENDU- OSLER